Pola Penggunanan Balanced Scorcard Pada Indikator Kinerja Utama Universitas Islam Negeri Syarif Hidayatullah Jakarta - Fitriadi Fitriadi; Mahendro Sumardjo; Jubaedah Jubaedah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
Abstract. The research problems about phenomena of the difficulty in seeing performance achievements and performance measurements at State Islamic University (UIN) Syarif Hidayatullah Jakarta. The UIN Syarif Hidayatullah Jakarta has difficulty making decisions in performance management, because before using the KPI, Its used budget management in performance appraisal and measurement. This research uses a qualitative method of field study with a phenomenological approach. Research objects are the experiences of the use of the Balanced Scorecard (BSC) pattern on the KPI of the UIN Syarif Hidayatullah Jakarta in 2018. After its existence of the Main KPI using the BSC. The results of the KPI are taken into consideration for performance evaluation by stakeholders at UIN Syarif Hidayatullah Jakarta in achieving the organization's vision. This performance appraisal and performance measurement can serve as a reference for performance achievements for Higher Education Rankings at the national and international level, Government Institution Performance Accountability Report (LAKIP), Strategic Plan (Renstra) and Campus Development Master Plan (RIBKA) or Milestones by looking at indicators, targets and size of the report.Keywords: Key Performance Indicators (KPI), Key Performance Indicators (KPI), Balanced Scorecard (BSC), Performance Measurement, Cascade. Abstrak. Fenomena yang diteliti pada UIN Syarif Hidayatullah Jakarta adalah sulitnya melihat capaian kinerja dan pengukuran kinerja. Oleh karena itu, UIN Syarif Hidayatullah Jakarta kesulitan mengambil keputusan dalam manajemen kinerja, sebelum menggunakan IKU, UIN Syarif Hidayatullah Jakarta menggunakan manajemen anggaran dalam penilaian dan pengukuran kinerja. Penelitian ini menggunakan metode kualitatif studi lapangan dengan pendekatan fenomenologi. Yang diteliti adalah pengalaman pola penggunaan Balanced Scorecard (BSC) IKU atau Key Performance Indicator (KPI) UIN Syarif Hidayatullah Jakarta tahun 2018. Setelah adanya IKU di UIN Syarif Hidayatullah Jakarta dengan menggunakan Balanced Scorecard (BSC). penilaian kinerja dan ukuran kinerja ini bisa sebagai acuan capaiaan kinerja untuk Perangkingan Perguruan Tinggi di tingkat nasional maupun internasional, Laporan Akuntabilitas Kinerja Instansi Pemerintahan (LAKIP), Rencana Strategis (Renstra) dan Rencana Induk Pengembangan Kampus (RIBKA) atau Milestones dengan melihat indikator, target dan ukuran pada lapran tersebut.Kata Kunci: Indikator Kinerja Utama (IKU), Key Performance Indicator (KPI), Balanced Scorecard (BSC), Pengukuran Kinerja, Cascade.